(untitled) (The International Journal for Scientific Research, 2026)
This research evaluates the development of Geometric thinking competencies of secondary students for (85) students in the Education Directorate of "Baghdad/ Karkh – III" for the academic year (2024/2025). This was achieved by training them on an educational unit based on active learning strategies and artificial intelligence (AI) applications, as well as preparing a test for geometric thinking competencies according to the skills of (visualization, analysis, inference, understanding relationships, and creativity and innovation) and monitoring their responses to a test in geometric thinking competencies, The test was constructed by the researcher based on "Van Hiele’s hierarchical framework" of Geometric thinking, in addition to verifying its psychometric properties. The results classified students within the defined geometric thinking competencies, and also showed that applying the educational unit according to active learning strategies and artificial intelligence (AI) applications had an impact. The researcher recommended redesigning Geometry units in light of the teaching and learning model proposed by "Van Hiele Framework" including its descriptive and inferential skills, and studying the impact on the development of geometric thinking levels among students.